Data Analysis Sheet For Determining The Position Pixel / Dot On Panel LED P10 - Hilmi Hilmi; Susanty W (Bandar Lampung University (UBL), 2017)
Traffic congestion is a major problem in the transportation system. Based Data Transport Statistics 2013 & 2014 are sourced from Statistics Indonesia (BPS Catalog: 8301007) cite an increase in the number of vehicles is high at 10.39 per cent per year on all types of vehicles. Coupled with the specific transportation community awareness so that adds a level of congestion becomes worse. Signs and traffic lights play an important role in regulating the traffic lane so that the public transport can be wise in using the road, especially in the port city of Lampung.